2022
DOI: 10.1039/d2nj01587k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable dihydrophenazine-based polymer from industrial waste as a sustainable lithium-ion battery cathode material

Abstract: Fully utilization of chemical industrial wastes is critical to the ecological and social sustainability. Amongst, it is rather fascinating to utilize redox-active organic wastes as sustainable electrode materials for rechargeable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For example, the 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) radical, a well-studied redox-active group, has been appended to polyacrylamide, polymethacrylate, polyether, polynorbornene, polystyrene, and polypeptide backbones. Similar backbone diversity can be found with other popular motifs, such as quinones and phenazines. In all cases, the backbone’s physical attributes, such as its degree of crystallinity, flexibility, and polarity, are transferred to the OEM. This, in turn, dictates the morphology and dynamics within the electrode film and, ultimately, strongly influences the device performance.…”
Section: Introductionmentioning
confidence: 67%
“…For example, the 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) radical, a well-studied redox-active group, has been appended to polyacrylamide, polymethacrylate, polyether, polynorbornene, polystyrene, and polypeptide backbones. Similar backbone diversity can be found with other popular motifs, such as quinones and phenazines. In all cases, the backbone’s physical attributes, such as its degree of crystallinity, flexibility, and polarity, are transferred to the OEM. This, in turn, dictates the morphology and dynamics within the electrode film and, ultimately, strongly influences the device performance.…”
Section: Introductionmentioning
confidence: 67%
“…In general, polymerization of the active materials is the commonly used strategy to mitigate the dissolution problem of organic materials. [128][129][130][131] For example, Dai et al demonstrated that the superior stability of N redox-active centers in N,N'-diphenyl-5,10-dihydrophenazine oligomer (p-DPPZ) was achieved by conjugation manipulation. [55] The DFT calculations disclose that the p-DPPZ possesses donor-acceptor-donor chain and cationacceptor-cation chain structure in natural and charged state, respectively.…”
Section: Dihydrophenazine Derivativesmentioning
confidence: 99%
“…valuable materials for suitable OEMs is critical and benecial. [12][13][14] Phenazine is a main component of the dregs in the production of rubber antioxidant RT-base. The annual output of phenazine in RT-base dregs is more than 1000 tons in China alone.…”
mentioning
confidence: 99%
“…Therefore, the exploitation of industrial wastes as valuable materials for suitable OEMs is critical and beneficial. 12–14…”
mentioning
confidence: 99%
See 1 more Smart Citation